Proinflammatory cytokines and thrombomodulin in patients with peptic ulcer disease and gastric cancer, infected with Helicobacter pylori - Mehrdad Haghazali; Mahsa Molaei; Reza Mashayekhi; Homayoun Zojaji; Mohammad Amin Pourhoseingholi; Tina Shooshtarizadeh; Dariush Mirsattari; Mohammad Reza Zali (Wolters Kluwer Medknow Publications, 2011)
Backgrounds: Helicobacter pylori infect more than half of the global population. It is suggested to be related with gastritis, peptic ulcer disease (PUD), and gastric cancer. Aims: The aim of this present study was to evaluate proinflammatory cytokines including interleukin 1, 6, 8, 10, and thrombomodulin in H. pylori-infected patients with PUD and gastric cancer. Patients: This cross-sectional study was conducted in Taleghani Hospital on 111 patients with H. pylori infection. Materials and Methods: Patients were divided into three groups of PUD, cancer, and control (normal on endoscopy), according to the results of endoscopy. The serum levels of interleukins 1, 6, 8, and 10 and thrombomodulin was determined using enzyme-linked immunosorbent assay (ELISA) technique. H. pylori infection was diagnosed by histological examination of the endoscopic biopsy. Results: One hundred eleven patients were included in the study; 30 as PUD group, 30 as gastric cancer group, and 51 as controls. There was no significant difference between the means of IL-1 and IL-10 levels among the three groups (P = 0.744 and 0.383, respectively). IL-6, IL-8, and thrombomodulin levels were found to be statically different among the three groups (P < 0.05). The level of IL-6, IL-8, and thrombomodulin in cancer group was significantly higher than PUD and control groups (P < 0.05). Conclusion: There is a significant association between H. pylori infection and serum IL-6, IL-8, and thrombomodulin but such relation is not present between H. pylori and IL-1 and IL-10. Immunity response (IL-6, IL-8 and thrombomodulin) is more severe in cancer patient than PUD.